S100 Impact of influenza near-patient testing on admissions and antimicrobial use: a single scottish centre experience. (December 2018) - Tate, M; Spears, M; Beckett, D; Baggott, A; Medhi, M; Cooke, B
Abstract : Introduction: Seasonal influenza leads to an increase in acute presentations to hospital. The infectious nature of influenza mandates source isolation of confirmed and suspected admitted cases, and national guidelines recommend antiviral use in confirmed influenza. Early diagnosis of influenza using near-patient testing (NPT) should optimise use of limited infection-control resources as well as improve antimicrobial use. Methods: NPT using a real-time PCR (polymerase-chain reaction) system was trialled at our centre between December 2017 and April 2018. A retrospective analysis of cases identified as Influenza A/B positive was performed using data from electronic records. Characteristics of the entire trial population were analysed, with a more detailed analysis of two samples (first 100 cases (cohort 1); final 100 cases (cohort 2)). In addition, a retrospective analysis of lab-confirmed influenza cases (n=98) from the same period during 2016–2017 was performed to assess the impact of NPT. Results: 2205 tests were performed during the trial period, with 710 (32%) positive tests. 446 (21%) of samples were positive for Influenza A, 220 (11%) were positive for Influenza B. Comparison with the previous year showed clear improvement in admission characteristics and antimicrobial prescribing (see table 1). Over the course of the trial, there were also positive changes in admission rates and antibiotic prescribing. Only 5.8% of NPT-positive samples were sent for confirmatory conventional lab PCR, all of which were positive. An additional 39 cases were identified with lab testing – it is unclear whether these cases were false-negative by NPT or were not tested. Conclusion: Respiratory virus NPT in a district general hospital setting appears to improve antiviral prescribing, reduce inappropriate antibiotic prescription and improve isolation facility utilisation compared to standard laboratory testing. Future work should focus on identifying the most appropriate patient groups for rapid diagnostic testing and improving antibiotic prescribing.